Faculty Members’ Technological Integration Effectiveness and Students’ Performance: An overview of the Perceptions of University Teachers - Kausar, Fahd Naveed; Anwar, Shaina; Kulsoom, Saima; Butt, Faiza Unsar (Pakistan Journal of Humanities and Social Sciences, 2023)
The objective of the study was to find out the Perceptions of Faculty Members’ Technological Integration Effectiveness and Students’ Performance at the University Level.Students from all public and private universities in the Lahore district made up the population. The instruments of the study were questionnaires. The sample was collected through the multistage simple random sampling technique. Through Cronbach's Alpha, the instrument's reliability was evaluated. Expert opinion guaranteed the instrument's validity. A descriptive technique was used to analyze the data. While summing up the results of the findings, technology integration has a mean of 4.05 and a standard deviation of 0.468. Performance among students has a mean of 4.03 and a standard deviation of 0.554 which indicates that faculty members’ perceptions reflected the level of agreement. It was finally encompassed that teachers’ behaviour towards technological integration in higher education is necessary for students’ performance i.e. class participation, class achievement self-confidence etc. This research recommended that sessions on technology integration should be considered vital and included as a clear framework throughout the entire syllabus.